Tele-ecografia obstétrica: análise das imagens ultrassonográficas do primeiro trimestre transmitidas/recebidas em tempo real - Ferlin, Rejane Maria (2010)
To determine the diagnostic accuracy of the ultrasound images in the first trimester (Head-Buttock Length and Nuchal Translucency) transmitted / received in real time. Caustics and Methods: A prospective cohort study of fetal ultrasonographic images of pregnant women over 18 years of age obtained between 11 and 13 weeks plus six days of pregnancy. The exams were transmitted in real time to three independent observers certified by the Fetal Medicine Foundation who performed the qualitative assessment. Copies of the received images were sent by the evaluators to support the quantitative analysis through ImajeJ software. Results: All fetal structures could be visualized and identified and the quality of the images received was considered regular by the evaluators. The quantitative analysis showed a reasonable loss in the number of pixels in relation to the original image. Conclusion: The quality of the transmitted images, through the use of softwares and low cost or free programs, allows the implementation of a multicenter study, through tele-ecography, aiming at an Internet transmission / reception protocol, with the aim of popularizing the chromosomal changes in the first trimester of gestation.